The Lack of Regulations on the Mechanism for Terminating Investigations by the Directorate of General Criminal Investigation of the Regional Police in Handling General Crimes - Tri Satrio Sulistomo; S Suparno (Indonesian Journal Publisher, 2026)
In order to ensure that a criminal case is only continued if it satisfies the legal standards and has adequate evidence, investigators in the criminal justice system have the right to terminate an investigation. The Criminal Procedure Code, specifically Article 109 paragraph (2), governs the termination of investigations in Indonesia. If there is insufficient evidence, the incident does not constitute a crime, or the termination is mandated by law, investigators may end an investigation. However, these regulations are still general in nature and do not regulate in detail the procedures, standards for evaluating evidence, or oversight mechanisms for terminating an investigation. In order to achieve legal certainty in the investigation process, this study intends to analyze the issues surrounding the termination of investigations in investigative practices by investigators at the Directorate of General Criminal Investigation within the Regional Police and develop a reconstruction of legal regulations. This study uses a normative juridical legal research methodology that combines an analytical and statutory approach. The study results indicate that the absence of more detailed regulations regarding the mechanism for terminating an investigation has the potential to lead to differences in investigator interpretation, a lack of transparency in decision-making, and an increase in legal disputes through pretrial mechanisms. Therefore, strengthening legal regulations is necessary through the formulation of evidence evaluation standards, internal oversight mechanisms, and mandatory transparency in decisions to terminate investigations to ensure legal certainty and accountability in the criminal justice system.